IRON ABUNDANCES IN THE ATMOSPHERES OF HD10700 and HD146233 - Ivanyuk, O. N.; Pavlenko, Ya. V.; Jenkins, J. S.; Jones, H.R.A.; Lyubchik, Yu.; Kaminsky, B.; Kuznetsov, M. (Одеські астрономічні публікації, 2010)
There are many different means to determine physical parameters of stars and their abundances by spectral analysis. In our work we draw our attention to the rotational and microturbulenc velocities as well as metallicities for the stars of known effective temperature and surface gravity. We carried fits of LTE synthetic spectra to the observed spectra of HD10700 and HD146233. These stars are knows aa solar-twins except slightly higher rotational velocities in both cases and higher magnetical activity i of HD10700. We adopted ABEL software (Pavlenko Ya.V.) to fit to HD10700, HD146233 spectra obtained on Camino Observatory, Chilie. Selected stars looks like. We compare our results with previous work of Valenti and Fischer (2005).